Analysis and Assessment of Motivational, Innovative and Investment Conditions for Implementing Renewable Energy Carpathian Enterprises - Петренко, В. П.; Палійчук, У. Ю.; Ільницький, Д. Є. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
To make a comparison analysis of the use of unconventional and renewable energy sources for the provision of business activity of enterprises of the Carpathian region, it has been suggested to implement such evaluation indicators as the ratio of the energy generated from these sources to 1 million of population, and also the coefficient of deviation of the ratio form the corresponding ratio in the EU. As a result, it has been damonstrated that in Ukraine and in the Carpathian region the drawbacks of management of innovational and investment processes by management authorities of enterprises, industries, region and state art the main obstacles of mass implementation of renewable energy.